Reducing greenhouse gas emissions of Amazon hydropower with strategic dam planning - Rafael M. Almeida (Nature Portfolio, 2019)
Some dams produce large amounts of GHGs and it is important to see whether future dams will satisfy sustainable energy goals. Here the authors estimate the range of GHG emission intensities expected for 351 proposed and 158 existing Amazon dams and find that existing Amazon hydropower reservoirs collectively emit 14 Tg CO2eq per year, and that if all proposed Amazon dams are built, annual emissions would increase 5-fold.